LITERARY AND SCIENTIFIC REVIEW OF LEECH THERAPY IN AYURVEDA AND MODERN SCIENCE - Gupta, *Sanjaya; Patil, Siddhanagouda; Patil, Vasant; Singh, Shipra (International Journal of Ayurveda and Pharma Research, 2017)
Leech Therapy is claimed to be the supreme therapy because of its high efficiency in the curing blood related disorders. According Ayurvedic classics it is safer and less complicated natural process therefore indicated even for the king, rich, old, fearful, weak, women, and the people of tender nature. Records of the medical usage of leeches date back to the beginning of civilization. Modern hirudotherapy differs from that of ancient one because now we do not use wild leeches but grown in a special bio factories where they are in severe quarantine. Except, now a days the leeches used only once. After using a leech it is destroyed this fact excludes infection of the patients. The absolute safety and obvious advantage of hirudotherapy and checked up by thousands of years of experience of mankind and does not cause any doubt in the secretion of medicinal leeches salivary gland, except hirudin inhibitor of ferment thrombin, there is a whole range of biological active combinations. The benefits of leech therapy were earlier thought to be derived from the amount of blood lost, hence relieving congestion and removing the noxious humors. Recent researches have demonstrated that more than the blood loss, it is the salivary secretions of the leech which contain an amazing cocktail of medicinal substances. This has led to its therapeutic use in numerous medical and surgical conditions like varicosities, various skin diseases like scabies, psoriasis, ringworm etc; phlebitis, to reduce post-operative swelling in plastic and reconstructive surgery and pain relief in various arthritic diseases.